Correlation Between Traditional Folk Game "Hadang" and Motor Skills Development Among Elementary School Students - Lukas Alexander Situmorang; Bayu Saputra; Ody Pratama Elmahdi; Nurfadillah Siregar; Nopi Hardiyanto; Nuraini Nuraini; M. Syahputra M. Syahputra; Alan Alfiansyah Putra Karo Karo (Joska: Jurnal Isori Kampar, 2025)
Objectives: This research aimed to investigate the correlation between participation in the traditional Indonesian folk game "Hadang" and motor skill development among elementary school students at SD Negeri 064006 Medan City. Methods: A cross-sectional correlational study was conducted with 120 students (ages 6-12 years) from SD Negeri 064006. Motor skills were assessed using the Test of Gross Motor Development-3 (TGMD-3) and fine motor skills evaluation. Hadang game participation was measured through structured observation and participation frequency questionnaires over 12 weeks. Results: Strong positive correlations were found between Hadang game participation and gross motor skills (r = 0.76, p < 0.001), agility (r = 0.68, p < 0.001), and coordination (r = 0.72, p < 0.001). Students with regular Hadang participation showed significantly higher motor skill scores compared to non-participants. Conclusion: Traditional folk game Hadang demonstrates significant positive correlation with motor skill development in elementary students, suggesting its potential as an effective physical education intervention.